Visualizing the Incantatory Power of the Sijundai Ritual: A Reinterpretation of Magical Phenomena through the Dance Work Migrasi Magis - Ariefin Alham Jaya Putra; Fattahul Anugraha; Zulfikar Rizki Ananda; Suaida Suaida (LPPM Institut Seni Indonesia Padangpanjang, 2025)
Migrasi Magis is a research-based dance creation that reinterprets the Sijundai magical phenomenon in Minangkabau culture. The ritual involves the use of spells and saluang music believed to possess supernatural power that psychologically and physically affects victims. Through observation, exploration, improvisation, formation, and evaluation, the artist transforms elements of space, time, energy, and property into visual symbols of the spell’s potency. The reinterpretation approach transforms this spiritual practice into an artistic expression through dance theatre, marked by dramatic tension, symbolism, and emotional intensity. The work embodies magical aesthetics derived from traditional rituals while portraying human desires, vengeance, and remorse. Migrasi Magis demonstrates how dance serves as a reflective space for social, spiritual, and psychological phenomena within Minangkabau society. Field data were collected through interviews with shamans, performance observations, and literature review, strengthening conceptual validity, aesthetic choices, and cultural context. This work illustrates that performing arts can negotiate tradition and modernity through contextual artistic interpretation